Ciri-ciri antena bowtie - Faizal, Adly Farriz (2005)
One needs to have a great understanding in electromagnetic theory in order to construct or build an antenna. The use of appropriate computer applications, as an aid in computer modelling is also very important. The use of these computer applications would help in doing antenna modelling before the real antenna is being constructed. This would also enables the determination of antenna parameters and having the antenna to be analysed at first. In this research, a type of a broad band antenna which is the bowtie antenna with the centre frequency of 1 GHz had been build and studied. The study on this antenna mainly concentrates on one of its electrical characteristics, which is the Return Loss as well as its electrical and magnetic field. This antenna was first being modelled using a computer application called LC, before the building of the real antenna according to mathematics calculation in theory and its model. From the Return Loss versus Frequency obtained from the antenna’s simulation results, its broadband characteristic was observed with its centre frequency of 1.1 GHz. Besides that, its electrical and magnetic field was also observed. Eventually, the test on the real antenna through experiment could not be done because the cost of items required is very high and shortage of test equipments. However, for future development, the use of other appropriate computer applications have to be ventured in order to be able to make antenna modelling much more easier, faster and accurate besides having all the required items and test equipments.